Corrosion Rate Analysis on SA 240 TP 904L Material Experience Multiple Repair - Muhammad Ari; Dika Anggara; Amar Sastra Adi (Politeknik Negeri Lhokseumawe, 2023)
Weld imperfections are likely to arise during any welding process. Due to the enormous number of joints that could result in weld defects, welding process faults could happen. Repair procedures are required to address welding defects. Multiple repairs are required if welding mistakes are made repeatedly. The duplex material used in this study is SA 240 TP 904L. By altering the repair procedure treatment 1x, 3x, 5x, and without repair, the welding process is carried out utilizing the SMAW method and E309L filler. Microstructure testing, ferrite content testing, and 3-electrode cell corrosion are the test techniques used. The relationship between the corrosion rate and the amount of ferrite content was deduced from the test data. The corrosion rate increases as the ferrite content rises due to several repairs.